2013
DOI: 10.5172/conu.2013.44.2.225
|View full text |Cite
|
Sign up to set email alerts
|

The wartime experience of civilian nurses in Iran–Iraq war, 1980–1988: An historical research

Abstract: Nurses' efforts and experiences and their outstanding achievement, contributes to our understanding of wartime nursing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 10 publications
3
17
0
Order By: Relevance
“…These effects, whether positive or negative, need special attention. A historical study conducted in in Iran by Firouzkouhi et al. showed that, although the majority of nurses were well able to adapt their care to the conditions of the wartime, they were not especially trained for wartime nursing.…”
Section: Introductionmentioning
confidence: 99%
“…These effects, whether positive or negative, need special attention. A historical study conducted in in Iran by Firouzkouhi et al. showed that, although the majority of nurses were well able to adapt their care to the conditions of the wartime, they were not especially trained for wartime nursing.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Biedermann et al reported that nurses that worked in Vietnam quickly adapted themselves despite the lack of clinical experience, inadequate preparation, fatigue and emotional trauma of their new environment (17). Also, Firouzkouhi et al found that the majority of nurses and rescuers, who joined the armed forces in the Iran-Iraq war, could quickly adapt with the condition despite having no previous training, and performed their task very well (3).…”
Section: Discussionmentioning
confidence: 99%
“…The Iran-Iraq war that began in September 1980 and ended in August 1988 inflicted enormous human costs, as each side sustained hundreds of thousands of casualties (3). Medical staff tried to treat the wounded during the war and were themselves not secure from injuries, and more than 4000 doctors, nurses, paramedics, and rescue work-ers, were killed (4).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has pointed to different nature of care in war (2). Studies found that wartime nursing is an integral part of the history of professional nursing, and greatest advances in the organization and professionalization of nursing have taken place during wartime (4). Very little has been written about the professionalization of healthcare disciplines in the wartime despite the importance of these historical times.…”
Section: Introductionmentioning
confidence: 99%
“…The Iran-Iraq war began in September 1980 and ended in August 1988 (4). During the war, Iranian healthcare staff, as well as combatants, experienced many difficulties and their efforts are not secret for anyone.…”
Section: Introductionmentioning
confidence: 99%